Batang Tekno a mission organization's "Boarding House" approach and the assimilation of Iraya Mangyan children and their families in Abra de Ilog, Occidental Mindoro - Danganan, Omega Diadem T. (2009)
This ethnography looks at the mission endeavors of a mission organization called Teknotropheo missions among the Iraya Mangyan children and families of Abra de Ilog, Occidental Mindoro. This mission group started their work among these Mangyans in 1998 and since then has established a relationship based on the participation of the Iraya Mangyan children and families in the different programs being carried out among them by the mission organization. Various ways by which Teknotropheo missions proved to be of help and services among these Mangyans were evident especially when the community experienced a crossfire incident in 2006 which eventually led them t resettle to another location closer to the town. Throughout the course of these events the Iraya Mangyan children and families have gained a high regard for formal education. This has resulted in new priorities for the community and the desire to make their children finish schooling. The Teknotropheo missions has scholarship program to assist education needs of the Iraya Mangyan children. One of its provisions is to house and feed these children at Teknotropheo Missions Development Center where training of behavior of the students - called "batang tekno" - are being performed by the staff members inside the institution. This kind of set-up reflects the notion of "total institution" coined by Goffman in the 1960s and supported by the ideas of Foucault (1977) with regard to how disciplining of bodies placed within a confined setting can produce new individuals and thus transformation (reformation) of members can be achieved. The following discussion shows that changes of behavior among batang tekno depend on how long the student stays at the instituion - whether they "stay-in" or go home after school to their families. The assertions established on this paper are also drawn from the insights of "practice theory" (Ortner 1994) to understand the engagement by the staff, the batang tekno, and their parents with the changing aspects observed in the lives of the batang tekno and their families. Remarkable among them is how their behaviors are becoming accustomed to the modern lifestyles of their lowland counterparts in town. The data from which this study was drawn is based from my own ethnographic investigation throughout my intermittent fieldwork visits in Mindoro in 2006 and 2007 using the following research methods: house survey, informal interviews, and participant observation.